Kurdish Hizbullah in Turkey Islamism, Violence and the State - Kurt, Mehmet (Pluto Press, 2017)
An academic insider's account of the Islamist social movement Kurdish Hizbullah.
Description based on print version record.
KU Select 2016 Front List Collection
Keywords: Social Science / Violence In Society; Social sciences; Electronic books